2024
DOI: 10.1037/pac0000694
|View full text |Cite
|
Sign up to set email alerts
|

Majority grievance in Germany: The role of entitlement beliefs and ingroup threat.

Mukadder Okuyan,
Lukas Loreth,
Frederike Stucke

Abstract: Group-based grievance has mainly been studied from the perspective of disadvantaged and minority groups. Following the refugee crisis and corresponding sociopolitical changes, there has also been an increase in perceived grievance among majority groups in many European countries. The present studies examined the role of perceived threat in the relationship between autochthony-based entitlement and group grievances among members of the German majority. Across three correlational studies, we tested whether threa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 54 publications
(90 reference statements)
0
3
0
Order By: Relevance
“…These results, while focused on nonviolent resistance, ironically correspond with the tragic current events in Israel, where residing near Israeli settlements and checkpoints has likely damaged the sense of social cohesion among the Palestinians and paved the way for violence between Palestinians and Israelis. Note that while the articles by Lee et al (2023), Okuyan et al (2023), and Ioku and Watamura (2024) considered perceived (ownership) threat, Penić et al (2023) captured territorial threat more objectively by modeling the This document is copyrighted by the American Psychological Association or one of its allied publishers.…”
Section: The Role Of Place In Ingroup Solidarity and Collective Actionmentioning
confidence: 99%
See 2 more Smart Citations
“…These results, while focused on nonviolent resistance, ironically correspond with the tragic current events in Israel, where residing near Israeli settlements and checkpoints has likely damaged the sense of social cohesion among the Palestinians and paved the way for violence between Palestinians and Israelis. Note that while the articles by Lee et al (2023), Okuyan et al (2023), and Ioku and Watamura (2024) considered perceived (ownership) threat, Penić et al (2023) captured territorial threat more objectively by modeling the This document is copyrighted by the American Psychological Association or one of its allied publishers.…”
Section: The Role Of Place In Ingroup Solidarity and Collective Actionmentioning
confidence: 99%
“…This is because members of these groups consider their high status as deserved, while the improvement of the disadvantaged groups’ status is perceived as undeserved (Reyna et al, 2006). In three correlational studies, Okuyan et al (2023) examined the link between autochthony beliefs and grievance perceptions among German participants while also accounting for the role of perceived threat to the ingroup from migrants. They found that Germans who endorsed the idea that first inhabitants of a country deserve more rights than those who arrived later perceived more threats to their ingroup (i.e., Germans without migration background) and, in turn, claimed more majority grievances.…”
Section: The Role Of Place In Intergroup Relationsmentioning
confidence: 99%
See 1 more Smart Citation